Predicted and measured resting metabolic rate of male and female endurance athletes - Thompson, J.; Manore, M. M. (Journal of the Academy of Nutrition and Dietetics, 1996)
OBJECTIVE: To measure the resting metabolic rate (RMR) of a group of endurance-trained male and female athletes and to compare it with values predicted using published equations. DESIGN: RMR was measured twice: 1 week apart for the men and approximately 1 month apart for the women. RMR was predicted using equations of Harris and Benedict, Owen et al, Mifflin et al, and Cunningham. SUBJECTS/SETTING: Subjects were 37 trained endurance athletes (24 men, 13 women) who had participated in studies previously completed in our laboratory. MAIN OUTCOME MEASURES: The primary outcome measure was the comparison of predicted RMR with measured RMR. An exploratory procedure for the determination of predictive variables in these athletes was also performed. STATISTICAL ANALYSES PERFORMED: The Root Mean Squared Prediction Error method was used to compare predicted RMR with measured RMR. The maximum R2 procedure method was used to determine the best possible combination of four variables that explained the largest amount of variance in RMR. RESULTS: The Cunningham equation was found to predict measured RMR most accurately (within 158 kcal/d for men and 103 kcal/d for women). Fat-free mass was the best predictor of RMR in men, whereas energy intake was the best predictor in women. APPLICATIONS/CONCLUSIONS: The Cunningham equation provides an accurate estimate of RMR when determining energy needs of highly active people. Equations specific to athletes need to be developed. Factors in addition to body weight, height, and age should be investigated as possible predictor variables in athletes.